Computational fluid dynamic modelling of an electric smelting furnace in the platinum recovery process - Bezuidenhout, Johan Jacobus (Stellenbosch : Stellenbosch University, 2008)
Thesis (MScEng (Process Engineering))--Stellenbosch University, 2008.